The Small, Slow and Specialized CRISPR and Anti-CRISPR of Escherichia and Salmonella - Touchon, Marie (Public Library of Science, 2010)

(untitled)
Prokaryotes thrive in spite of the vast number and diversity of their viruses. This partly results from the evolution of mechanisms to inactivate or silence the action of exogenous DNA. Among these, Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR) are unique in providing adaptive immunity against elements with high local resemblance to genomes of previously infecting agents. Here, we analyze the CRISPR loci of 51 complete genomes of Escherichia and Salmonella. CRISPR are in two pairs of loci in Escherichia, one single pair in Salmonella, each pair showing a similar turnover rate, repeat sequence and putative linkage to a common set of cas genes. Yet, phylogeny shows that CRISPR and associated cas genes have different evolutionary histories, the latter being frequently exchanged or lost. In our set, one CRISPR pair seems specialized in plasmids often matching genes coding for the replication, conjugation and antirestriction machinery. Strikingly, this pair also matches the cognate cas genes in which case these genes are absent. The unexpectedly high conservation of this anti-CRISPR suggests selection to counteract the invasion of mobile elements containing functional CRISPR/cas systems. There are few spacers in most CRISPR, which rarely match genomes of known phages. Furthermore, we found that strains divergent less than 250 thousand years ago show virtually identical CRISPR. The lack of congruence between cas, CRISPR and the species phylogeny and the slow pace of CRISPR change make CRISPR poor epidemiological markers in enterobacteria. All these observations are at odds with the expectedly abundant and dynamic repertoire of spacers in an immune system aiming at protecting bacteria from phages. Since we observe purifying selection for the maintenance of CRISPR these results suggest that alternative evolutionary roles for CRISPR remain to be uncovered.